'Everyone should do it': Client experience of a 12‐week dialectical behaviour therapy group programme – An interpretative phenomenological analysis. Issue 3 (19th June 2018) - Childs‐Fegredo, Jasmine; Fellin, Lisa
Abstract: Objective: There is a dearth of practice‐based evidence of adapted or 'DBT‐informed' transdiagnostic models, which could provide services and clinicians with information of what works and for whom, in which settings. This paper aims to bridge this gap by exploring the client experience of a 12‐week transdiagnostic dialectical behaviour therapy (DBT) group programme in a private psychiatric hospital. Method: Five participants with varied clinical diagnoses and previous therapeutic experiences were interviewed following completion of one or more of the same adapted DBT programme, comprising of the standard four modules over 12 weeks, including a weekly skills group and 1:1 therapy. Interpretative phenomenological analysis (IPA) was applied to give voice to the clients' lived experience of the group. Results: Three master themes were identified: 'Pre DBT: Crisis & Desperation'; 'In‐session: Belonging'; and 'The Real World: Living', each characterised by four sub‐themes, highlighting helpful and hindering factors of clients' current and previous therapeutic experiences. Conclusion: Overall this version of DBT in a transdiagnostic setting was experienced as helpful and positive by participants; main outcomes included being able to build a life worth living, feel hope and joy, build DBT skills into a lifestyle, and develop reflective practice. Implications for clinical practice, service delivery and policy are also discussed. The article aims to provide clinicians with practice‐based evidence to inform the delivery of DBT as well as supporting the case for the use of DBT with various disorders, thus paving the way for future research in this area.